Key regulators of sensitivity to immunomodulatory drugs in cancer treatment - Shichao Wang; Zhiyue Li; Shaobing Gao (BMC, 2021)
Abstract Immunomodulatory drugs (IMiDs) include thalidomide, lenalidomide, and pomalidomide, which have shown significant efficacy in the treatment of multiple myeloma (MM), myelodysplastic syndrome (MDS) with deletion of chromosome 5q (del(5q)) and other hematological malignancies. IMiDs hijack the CRL4CRBN ubiquitin ligase to target cellular proteins for ubiquitination and degradation, which is responsible for their clinical activity in MM and MDS with del(5q). However, intrinsic and acquired resistance frequently limit the efficacy of IMiDs. Recently, many efforts have been made to explore key regulators of IMiD sensitivity, resulting in great advances in the understanding of the regulatory networks related to this class of drugs. In this review, we describe the mechanism of IMiDs in cancer treatment and summarize the key regulators of IMiD sensitivity. Furthermore, we introduce genome-wide CRISPR-Cas9 screenings, through which the regulatory networks of IMiD sensitivity could be identified.